Eagles – not vultures; corpse – not carrion. Notes on the margin of verses Mt 24:28 and Lk 17:37 - Salij, Jacek (The Bible as a meeting place for Christian denominations, 2022)
The author of the text devotes attention to the trap of etymological analogy, which is important from the point of view of translation, and affects the way the Gospel is interpreted. He focuses on the key Greek word το πτωµα (to ptõma) for the verse of Mt 24.28 and the word that is important for the verse Łk 17.37 το σωμα (to sõma). These words in Polish translations of the Gospels in the twentieth century began to be translated as “carrion”. According to the author, it was a wrong decision. Contrary to the words used in the source text, in Polish the word “carrion” is associated with emotionally negative feelings, while in the New Testament these words refer to the body of a dead person, often the Savior himself. The article also recalled Origen’s remarks in order not to overlook the detail that our logion talks about eagles, not vultures. According to the author, the false translation decision results in an almost profound closure to the rich tradition that the Fathers of the Church left in commenting on both verses.